ADAPTING COMMERCIAL LAW TO E-COMMERCE: NAVIGATING LEGAL FRAMEWORKS IN THE DIGITAL MARKETPLACE - Roaa Qasim Ayyal (International Journal of Business, Law and Political Science, 2024)
The digital transformation of commerce has precipitated a complex interplay between evolving business practices and the static nature of commercial law. The present research paper focuses on a rather interesting and noteworthy theme that is the adaptation of commercial law to the difficulties arising from the rapid growth of e-commerce. The research, which is centered on identifying the legal concerns that e-commerce businesses usually face, studies the scope of consumer disputes, intellectual property issues and regulatory compliance difficulties to determine the frequency of legal challenges. Data from 100 e-commerce businesses were submitted to SPSS for statistical analysis, and the aim was to find out significant predictors among the legal issues in the ecommerce sector. Descriptive stats lay out the distribution of legal problems, hence making it clear that the majority of business entities are not involved in many legal complexities. Correlation analysis showed no significant link between the number of legal cases and their presence of consumer disputes, indicating that the latter is not a reliable predictor. Regression analysis also confirms the non-significant statistical impact of the model predictors, as indicated by a very small R square value, showing that consumer disputes, intellectual property issues, and regulatory compliance do not substantially explain the variability in legal issues faced by e-commerce businesses. The outcomes point out the need for more complex and sophisticated consideration of the legal problems of e-commerce and the fact that there may be other factors not included that can be more vital. This very fact demonstrates the complexity of legal environment where e-commerce operates and the possibility of further variables, for example, more qualitative or context-sensitive, to add to the explanatory power. The study ends with a proposal of the further study of this multifaced legal issues in e-commerce and the development of a legal system which can more efficiently respond to the dynamics of digital trade.